Intercultural Workplace Interactions of Indonesian Expatriates in A Multicultural and Multinational Environment in Qatar - Sudarmanto Sudarmanto; Andika Putra Pratama (Journal Research of Social Science, Economics, and Management, 2026)
Intercultural interaction is inevitable for people who work abroad, and Indonesian expatriates working in Qatar are no exception. This study identified that Indonesian expatriates experienced culture shock and adaptation challenges during their first year of service in Qatar, and it proposes practical support mechanisms to improve workplace adaptation. Using a qualitative approach, data were collected from Indonesian expatriates through open-ended questionnaires and analyzed using thematic analysis supported by Hofstede's, Hall's, and Lewis's intercultural frameworks. The findings indicate that similarities between Indonesians' and Qataris' Hall High-Context cultural characteristics do not automatically ensure smooth adaptation. Differences in workplace communication, environmental context, language proficiency, mental resilience, soft skills, and access to country-specific information contribute to adaptation challenges. The study also identifies the importance of institutional and diaspora-based support. Therefore, this study recommends strengthening the role of the Indonesian Embassy in Doha and Indonesian diaspora groups through digital guidance channels, such as an interactive website, to support potential and newly arrived Indonesian expatriates in Qatar.